Two adolescents with unilateral cutaneous lesions - Marinho, Pedro; Teixeira, Susana Cláudia; Nogueira, Miguel; Machado, Susana (BIRTH AND GROWTH MEDICAL JOURNAL, 2024)
The authors report two cases of previously healthy male adolescents who presented with multiple unilateral telangiectatic macules without other associated cutaneous lesions. In one case, the telangiectasias had appeared 12 months earlier; in the other, they had been present since birth. The morphology and distribution pattern were consistent with unilateral nevoid telangiectasia, which is characterized by multiple unilateral telangiectasias arranged linearly by dermatome. The congenital form is rare, persists into adulthood, and is not associated with other vascular malformations. The acquired form resolves spontaneously after exclusion of the precipitating factor. Laser therapy is effective for unesthetic and/or persistent lesions.